2020
DOI: 10.3390/ijerph17082962
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin D3 Supplementation on Hepcidin, Iron, and IL-6 Responses after a 100 km Ultra-Marathon

Abstract: Deficiencies in iron and vitamin D are frequently observed in athletes. Therefore, we examined whether different baseline vitamin D3 levels have any impact on post-exercise serum hepcidin, IL-6 and iron responses in ultra-marathon runners. In this randomized control trial, the subjects (20 male, amateur runners, mean age 40.75 ± 7.15 years) were divided into two groups: experimental (VD) and control (CON). The VD group received vitamin D3 (10,000 UI/day) and the CON group received a placebo for two weeks befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 51 publications
(71 reference statements)
0
21
0
1
Order By: Relevance
“…From the articles that evaluated ultra-marathon running, four studies (Drenth et al, 1995 ; Donnikov et al, 2009 ; Gill et al, 2015a ; Benedetti et al, 2021 ) evaluated distances in the ranges of 51–86, 51–81, 122–208, and 99–218 km respectively, two studies (Mastaloudis et al, 2004 ; Díaz-Castro et al, 2012 ) 50 km distance, one study (Sansoni et al, 2017 ) 65 km distance, one study (Nieman et al, 2002 ) 80 km distance, one study (Peters et al, 2001 ) 90 km distance, four studies (Chiu et al, 2013 ; Czajkowska et al, 2020 ; Kasprowicz et al, 2020 ; Wołyniec et al, 2020 ) evaluated 100 km, four studies (Nieman et al, 2003 , 2005 , 2006 , 2007 ) evaluated 160 km, one study (Roupas et al, 2013 ) evaluated 180 km, one study (Kim et al, 2007 ) evaluated 200 km, one study (Gill et al, 2015b ) evaluated 230 km and one study (Shin and Lee, 2013 ) evaluated 308 km. Some studies that evaluated the ultra-marathons presented particularities in relation to the topography characteristic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the articles that evaluated ultra-marathon running, four studies (Drenth et al, 1995 ; Donnikov et al, 2009 ; Gill et al, 2015a ; Benedetti et al, 2021 ) evaluated distances in the ranges of 51–86, 51–81, 122–208, and 99–218 km respectively, two studies (Mastaloudis et al, 2004 ; Díaz-Castro et al, 2012 ) 50 km distance, one study (Sansoni et al, 2017 ) 65 km distance, one study (Nieman et al, 2002 ) 80 km distance, one study (Peters et al, 2001 ) 90 km distance, four studies (Chiu et al, 2013 ; Czajkowska et al, 2020 ; Kasprowicz et al, 2020 ; Wołyniec et al, 2020 ) evaluated 100 km, four studies (Nieman et al, 2003 , 2005 , 2006 , 2007 ) evaluated 160 km, one study (Roupas et al, 2013 ) evaluated 180 km, one study (Kim et al, 2007 ) evaluated 200 km, one study (Gill et al, 2015b ) evaluated 230 km and one study (Shin and Lee, 2013 ) evaluated 308 km. Some studies that evaluated the ultra-marathons presented particularities in relation to the topography characteristic.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies on trails with the varying ground (Mastaloudis et al, 2004 ; Roupas et al, 2013 ; Gill et al, 2015a , b ). Five studies with flat ground, including athletics tracks (Chiu et al, 2013 ; Czajkowska et al, 2020 ; Kasprowicz et al, 2020 ; Wołyniec et al, 2020 ; Benedetti et al, 2021 ), the other studies did not identify the running ground.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Kasprowicz et al, (2020) reported that both an excess and a deficiency of vitamin D can be detrimental to the selected health indices; therefore, future studies are needed to explore the association between the various doses of vitamin D3 supplementation and iron metabolism in athletes.…”
Section: Resultsmentioning
confidence: 98%
“…According to research, vitamin D 3 has a significant, beneficial effect on iron levels. In this way, it prevents the iron deficiency anemia that often affects athletes (Kasprowicz et al, 2020). In addition, a negative correlation has been noted regarding vitamin D 3 levels and markers of muscle damage.…”
Section: Factors Influencing Recovery and The Risk Of Injurymentioning
confidence: 96%